2021
DOI: 10.51679/ophiussa.2020.64
|View full text |Cite
|
Sign up to set email alerts
|

Foundry in the Late Bronze Age Baiões/Santa Luzia Cultural Group: some reflections starting from a new metallic mould for unifacial palstaves

Abstract: During the last quarter of a century, progress on the understanding of metallurgical practices of the Baiões / Santa Luzia cultural group of Central Portugal produced results that allowed us to better understand and characterize a fundamental cultural group of the Iberian Late Bronze Age (LBA). However, the study of the foundry moulds lacks a convenient interpretive synthesis.  The discovery of a new exemplar of metallic mould for single-faceted palstaves – one of the types that characterize Central Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Moulds to produce a wide range of metal objects, e.g., axes, sickles, chisels, spearheads, swords, bracelets, ornaments, etc., have been found across Europe [6][7][8][9][10] since the emergence of metallurgy. Moulds for axes are the most common ones, as also evidenced in the Iberian Peninsula [11][12][13][14][15]. They were produced with different materials-clay, stone, and metals-depending on the availability of raw materials and their specific properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moulds to produce a wide range of metal objects, e.g., axes, sickles, chisels, spearheads, swords, bracelets, ornaments, etc., have been found across Europe [6][7][8][9][10] since the emergence of metallurgy. Moulds for axes are the most common ones, as also evidenced in the Iberian Peninsula [11][12][13][14][15]. They were produced with different materials-clay, stone, and metals-depending on the availability of raw materials and their specific properties.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have proposed different dressing materials based on analysis of residues on Bronze Age mould artefacts: for example, one study suggested smoky flame from burning bones based on results from energy dispersive X-ray spectrometry (EDXRF), wet chemistry, Fourier transform infrared spectroscopy (FTIR), and gas chromatography mass spectrometry (GC/MS) from the black residue in a stone axe mould from Portugal [23]; another study proposed the use of beeswax based on results from FTIR and GC/MS from a black residue in a bronze axe mould from Poland [24]; finally, more recently, a blackish residue on the inner face of a Late Bronze Age mould from Portugal has been analysed by FTIR, revealing the use of clay or charcoal [14].…”
Section: Introductionmentioning
confidence: 99%